2013
DOI: 10.1590/s0080-623420130000400014
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre sintomas de insônia e artrite reumatóide em idosos

Abstract: INTRODUCTIONThe aging of the population is a worldwide phenomenon, highlighting the significant increase in the population aged 70 years and older. In 2009, the results of the National Household Sample Survey indicated a total of 11.3 million in this age group. The decrease of the children and youth and the consequent increase in adult population and elderly is related to the continued decline in the fertility and mortality rate combined with an increased life expectancy (1) .Simultaneously, the most prevalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Furthermore, this percentage is higher than the globally reported percentage among RA patients. Freitas et al3 used the Nottingham Health Profile and revealed that 55% of rheumatoid patients suffered from insomnia. This finding was explained by pain, functional disability, and depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this percentage is higher than the globally reported percentage among RA patients. Freitas et al3 used the Nottingham Health Profile and revealed that 55% of rheumatoid patients suffered from insomnia. This finding was explained by pain, functional disability, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality has been linked to pain, mood, fatigability, stress, and disease activity in the rheumatic disease population 1. Various primary sleep disorders have been observed in RA, including a high prevalence of obstructive sleep apnea (OSA),2 insomnia,3 and restless legs syndrome (RLS) 4. Abbasi et al5 determined that the frequency of sleep disorders among 100 RA patients is 72%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Convém destacar que outras características definidoras autorreferidas foram expressas pelos idosos, a exemplo de: sono não restaurador, redução na qualidade de vida, insatisfação com o sono, alteração no afeto, no humor e na concentração, estado de saúde comprometido e energia insuficiente. Tais características corroboram outros estudos e são responsáveis por grande insatisfação, além de prejudicar a saúde física, cognitiva e a qualidade de vida, principalmente, quando esses problemas estão associados às doenças, implicando negativamente na saúde das pessoas, especialmente das idosas [11].…”
Section: Discussionunclassified
“…Those expenses come from long term pharmacologic treatments, surgeries, physical rehabilitation, the loss of work days, both patients' and family members' who have to keep them company, and even from early retirements due to the patients' incapacity to fulfill their jobs' demands. Freitas et al (2013) state that pain and discomfort caused by RA can lead to serious consequences to the patients since they both contribute to the loss of functionality, and bad sleep quality, they undermine the patients' social participation, they have an important negative impact on people's health and well-being, especially when these people are older.…”
Section: Introductionmentioning
confidence: 99%